Placebo v protetiki in ortotiki - Burger, Helena (Rehabilitacija (Ljubljana), 2019)
Placebo and nocebo effects are effects of inert substances and inactive procedures that are usually used in control groups. Placebo can be any clinical intervention including words, gestures, pills, devices and surgery. Prostheses (mainly prosthetic components) and orthoses can also have placebo effect. All team members have to be aware of this, know the evidence about their effectiveness, be professional and not try to "sell" a product.
Keywords: orthoses; Orthotic Devices; ortoze; placebo; prostheses; proteze